Kombinasi Pijat Oksitosin dan Kapsul Jintan Hitam untuk Meningkatkan Kadar Hormon Prolaktin pada Ibu Postpartum dengan Seksio Sesarea - Yunita Dyah Fitriani; Syarief Thaufik H; Melyana Nurul W; Suhartono Suhartono (Jurnal LINK, 2015)
Research objectives analyze the effectiveness of combination oxytocin massage and black cumin capsules to increase the prolactin hormone levels in postpartum with sectio caesarean. Research methods quasi-experimental method non randomized controlled trial desain pretest posttest control group. The subjects are postpartum with sectio caesarean. It was chosen by purposive sampling. Analysis uses paired t-test and uses one-way anova. Results there were differences of prolactin hormone levels before and after given oxytocin massage (p=0.000). There were differences of prolactin hormone levels before and after given black cumin capsules (p=0.000). There were differences of prolactin hormone levels before and after given combination oxytocin massage and black cumin capsules (p=0.000). There were differences of prolactin hormone levels before and after controls (p=0.005). Conclusion the most effective of treatment to increase prolactin hormone levels is combination oxytocin massage and black cumin capsules. It is needed combination oxytocin massage and black cumin capsule to increase prolactin hormone levels.